Macroeconomic Effects of Crude Oil Price Movements: The Case of Nigeria - Hammed, Sulaiman Ayokunle (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Since the beginning of the 20th century till date, crude oil has played a major role as an indicator of economic growth, due to its immeasurable importance in supply of energy demand of the entire world. Over more than four decades, Nigeria has been an important crude oil exporter, her primary product. Crude oil production and export since 1957 has brought a tremendous change to the economy of Nigeria, contributing a large share to the gross domestic product of the country. As reported in Hamilton (2008), high and fluctuating oil prices have become an inevitable result of recent world developments such as strong growth in demand, contribution of scarcity rent and OPEC monopoly pricing. In the light of these, it is of interest to investigate how the Nigerian economy which is heavily dependent on the export of its primary product will be affected by such trends in the world. For the purpose, the study seeks to analyze various economic impacts caused by international fluctuations in crude oil prices on the Nigerian economy between1994Q.1 -2013Q.4 using quarterly data. Output growth and inflation variables have been used to reflect the state of the economy while money supply will capture the monetary policy response to real crude oil price movements. The analysis employs structural VAR methodology. The empirical results suggest a negative relationship between inflation and oil price shock and its volatility over the sample period while response of monetary policy is insignificant. However, both unexpected price shock and volatility imposes a positive impact on the Nigerian output which later may destabilize the economy. Keywords: SVAR, inflation, money supply and crude oil price.

Öz: Yirminci asrın başından günümüze dek, ham petrol, dünya enerji talebinin karşılanmasındaki rolü nedeniyle, ülkelerin ekonomik büyüme göstergeleri arasında önem kazanmıştır. Dört asrı aşkın bir süreden beri, Nijerya’nın en önemli üretimi olan petrol, ihracat yapısında da en üst sırada yer almıştır. 1957 yılından beri ham petrol üreticisi ve ihracatçısı olan Nijerya’nın ekonomisi, bu sayede değişim göstermiş ve petrol geliri gayri safi milli hasıla (GSMH) içinde önemli bir paya sahip olmuştur. Hamilton’nun (2008) belirttiği üzere, gerek petrola olan küresel talebin artması, gerekse, kaynakların azalıyor olması ve rant ile OPEC ülkelerinin tekel fiyatlaması gibi dünyadaki en son gelişmeler sonucunda, petrol fiyatlarındaki yüksek seyir ve dalgalanmalar kaçınılmaz olmuştur. Bu çerçevede, ekenomisi petrol ihracına bağimlı olan Nijerya’nın, sözkonusu gelişmelerden nasıl etkilenmekte olduğu, çalışmanın ilgi odağı olmuştur. Çalışmada, uluslararası petrol fiyatlarındaki artış ve dalgalanmaların, 1994Q.1 – 2013Q.4 döneminde Nijerya ekonomisi üzerindeki etkileri yapısal VAR (SVAR) yaklaşımı uygulaması ile araştırılmıştır. Nijerya ekonomisi için makroekonomik göstergeler olarak büyüme ve enflasyon, para politikasının tepkisini ölçmek amacıyla ise para arzı kullanılan değişkenler olmuştur. Elde edilen ampirik bulgulara göre, petrol fiyatlarındaki artış ve dalgalanma, Nijeryadaki enflasyonun azalmasına neden olurken, para politikasını etkilememektedir. Dünya petrol fiyatlarındaki artış ve dalgalanma ekonomik büyümeyi olumlu etkilemekle birlikte, ileride ekonomide dengesizliğe neden olabileceği sonucuna varılmıştır. Anahtar Kelimeler: SVAR, enflasyon, para arzı ve ham petrol fiyatı.
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2014. Supervisor: Assoc. Prof. Dr. Gülcay Tuna Payaslıoğlu.
Keywords: Economics; Petroleum industry and trade; Nigeria; Economic Conditions; Electric power production; SVAR; inflation; money supply and crude oil price